The History of Defining Youth: Current Implications for Identifying and Treating Delinquent Youth - Hartinger-Saunders, Robin M. (2008)
This article presents a historical overview of how legally and socially constructed definitions of childhood and youth have, and continue to, shape the identification, treatment and research surrounding delinquent youth. Even though we age biologically along a continuum, formal social systems, most notably the courts and our system of rights, are based on specific chronological age parameters which impose a rigid element to something that is otherwise fluid. This often results in subjective decision making regarding sanctions and treatment options among family and criminal court systems as well as other professionals who work closely with delinquent youth. This article highlights the importance of considering more than the specific delinquent act in determining the fate of youth. Consideration of individual characteristics and environmental factors will bring us closer to a more comprehensive strategy including intervention efforts to the family and community/ neighborhood level to stimulate long term change